Alien Plant Invasion: Are They Strictly Nature’s Enemy and How Can We Use Their Supremacy? - Lenka Bobuľská; Lenka Demková; Gabriela Pinčáková; Tomáš Lošák (Land)
The invasion of plant species is considered to be one of the most dangerous forces in biodiversity change and alteration of soil properties. Due to their significant impact on ecology and the economy, it is important to find an effective approach to manage invasive plant expansion and utilize them as a beneficial biomass source. This review focuses on the characterization of the negative and positive features of invasive plant species in general. Most studies focus on invasive species removal and lack an evaluation of their potential in modern biotechnologies. Currently, there are studies aimed at investigating their use in soil remediation, medicine, the chemical industry, the textile industry, and even gastronomy. Based on these reviews, we bring forward possible future developments in this research field which might serve as a theoretical premise for further research.